Frequency of Different Dermatosis Presented at OPD in Sir Syed Hospital Qayoomabad - Asia Hafeez, Shabnam Rani, Beenish Faisal, Priya Kumari Maheshwari, Abdul Haq Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of different dermatosis presented at OPD during one year at Sir Syed Hospital Qayyumabad. Methods: This retrospective study was conducted at dermatology OPD of Sir Syed hospital Qayoomabad. A one-year data of the patients who were presented with different dermatosis during January 2018 to December 2018 of either gender was studied to observe the commonest dermatological disease during these 12 months. A self-made questioner was used for the data collection and SPSS version 26 was used for the analysis of the data. Results: A total of one-year of retrospective data regarding dermatological diseases was studied. The average age of the patients was found 30.23+12.22 years. Females were in majority 1942(66.4%), while males were 982(33.6%). Dermatological disease mostly observed during July to December. Acne, Scabies, Urticaria, Tinea corporis, Acne vulgaris, Melasma, Tinea cruris and Eczema were found frequently high. Acne was most common from February to October, scabies was most common from May to December, Melasma was most common from June to December, furuncles were most common from June to July, Pityriasis versicolor was most common from September to October, and Tinea cruris was most common from July to November (p0.001). Conclusion: As per the study conclusion, the young females mostly visited the dermatology OPD. Acne, Scabies, Urticaria, Tinea corporis, Acne vulgaris, Melasma, Tinea cruris, and Eczema were observed to be the most frequent diseases, and the disease frequency observed varied as per seasonal variations.